The Main Factors, Modern Conditions and Directions of the Creation of Architectural Environment - Vadym Abyzov (Recent Developments in Engineering Research Vol. 12, 2021)
Definition of the numerous factors and conditions of sustainable development as paradigm of the shaping space in the XXI century is the subject of this study. The purpose of this research is an attempt to identify and analyse the modern conditions and impacts of the creation of architectural environment and on this basis to determine the main directions and tasks of the development of architecture at the appropriate hierarchical levels. A comprehensive review and structural analysis of all impact factors and different current conditions that lead to the sustainable architecture design are conducted in the proposal. The main groups of factors and conditions such as social-economical, natural-geographic, urban, ergonomics, ecological, typological, technical, cultural, and aesthetics are determined in accordance with their contemporary specifics. Special influence of different conditions of modern sustainable development were characterized. This analysis provides an opportunity to define the appropriative hierarchical levels of the modern trends and prospects of creation an effective, attractive and friendly architectural environment. Some examples of author’s projects and implementations is presented in the article. Such methodological approach will help to create a holistic view of the creation architectural environment, will allow to systematize existing knowledge’s and concepts, practices and prospects of the means and methods of its formation and development.